Investigation of fatigue crack propagation mechanisms of branching crack in 2324-T39 aluminum alloy thin plates under cyclic loading spectrum. (January 2016) - Zhang, Ting; Bao, Rui; Lu, SongSong; Fei, Binjun
Highlights: Significant crack branching was observed in VA and spectrum loading condition. There is a direct correlation between the crack path and fracture characteristics. The fracture mode and secondary cracks led to the appearance of branched cracks. High level σx, σz leads to mix-mode growth of the secondary cracks. Abstract: Significant macroscopic crack branching has been observed in the crack growth paths of 2324-T39 aluminum alloy under spectrum loading, the mechanisms of which was investigated in this paper. The relationships between microscopic fracture surface characteristics and macroscopic fatigue crack growth paths and the relationship between plastic zone size and fracture surface characteristics were revealed. The change in fracture mode, which relates to the changes in the plastic zone in the thickness direction, and the growth of secondary cracks led to the appearance of branched cracks. A high level of σx, σz leads to mixed-mode growth of the subsurface secondary cracks.